Terveydenhuoltotutkimus Suomessa vuonna 1988 : sisällön analyysi - Eklund, Leena ([Helsinki] : Helsingin yliopisto, 1991)
Summary.
Keywords: Health Services Needs and Demand; Health Services Research; terveydenhuolto; tutkimus; hälso- och sjukvård; forskning